The effect of patient point of entry and Medicaid status on quality outcomes following total hip arthroplasty. (July 2020) - Roof, Mackenzie A.; Feng, James E.; Anoushiravani, Afshin A.; Schoof, Lauren H.; Friedlander, Scott; Lajam, Claudette M.; Vigdorchik, Jonathan; Slover, James D.; Schwarzkopf, Ran
Abstract : Aims: Previous studies have reported an increased risk for postoperative complications in the Medicaid population undergoing total hip arthroplasty (THA). These studies have not controlled for the surgeon's practice or patient care setting. This study aims to evaluate whether patient point of entry and Medicaid status plays a role in quality outcomes and discharge disposition following THA. Methods: The electronic medical record at our institution was retrospectively reviewed for all primary, unilateral THA between January 2016 and January 2018. THA recipients were categorized as either Medicaid or non-Medicaid patients based on a visit to our institution's Hospital Ambulatory Care Center (HACC) within the six months prior to surgery. Only patients who had been operated on by surgeons (CML, JV, JDS, RS) with at least ten Medicaid and ten non-Medicaid patients were included in the study. The patients included in this study were 56.33% female, had a mean age of 60.85 years, and had a mean BMI of 29.14. The average length of follow-up was 343.73 days. Results: A total of 426 hips in 403 patients were included in this study, with 114 Medicaid patients and 312 non-Medicaid patients. Medicaid patients had a significantly lower mean age (54.68 years (SD 12.33) vs 63.10 years (SD 12.38); p < 0.001), more likely to be black or 'other' race (27.19% vs 13.46% black; 26.32% vs 12.82% other; p < 0.001), and more likely to be a current smoker (19.30% vs 9.29%; p = 0.001). After adjusting for patient risk factors, there was a significant Medicaid effect on length of stay (LOS) (rate ratio 1.129, 95% confidence interval (CI) 1.048 to 1.216; p = 0.001) and facility discharge (odds ratio 2.010, 95% CI 1.398 to 2.890; p < 0.001). There was no Medicaid effect on surgical time (exponentiated β coefficient 1.015, 95% CI 0.995 to 1.036; p = 0.136). There was no difference in 30-day readmission, 90-day readmission, 30-day infections, 90-day infections, and 90-day mortality between the two groups. Conclusion: After controlling for patient variables, there was a statistically significant Medicaid effect on LOS and facility discharge. These results indicate that clinically similar outcomes can be achieved for Medicaid patients; however, further work is needed on maximizing social support and preoperative patient education with a focus on successful home discharge. Cite this article: Bone Joint J 2020;102-B(7 Supple B):78–84.